2012
DOI: 10.5301/jbm.2012.9314
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic score based on clinical factors and biomarkers for advanced non-small cell lung cancer

Abstract: The application of a score that includes clinical data and biomarkers may improve the prognostic classification of NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Trape et al developed an AFP scoring system that revealed similar results to our study. In their study, the median OS rates of patients who received CT were 15, 7, and 5 months in AFP 0–1, AFP 2–3 and AFP 4–5 groups, respectively, versus 8, 6, and 2 months in patients who did not receive any CT [8] . The median PFS was 10 months in the LPI 0 group and 5 months in the LPI 2 group.…”
Section: Discussionmentioning
confidence: 92%
“…Trape et al developed an AFP scoring system that revealed similar results to our study. In their study, the median OS rates of patients who received CT were 15, 7, and 5 months in AFP 0–1, AFP 2–3 and AFP 4–5 groups, respectively, versus 8, 6, and 2 months in patients who did not receive any CT [8] . The median PFS was 10 months in the LPI 0 group and 5 months in the LPI 2 group.…”
Section: Discussionmentioning
confidence: 92%
“…The authors suggested that albumin and LDH levels might be used in the risk scoring in further studies. Further studies demonstrated that serum albumin level was a critical prognostic factor in the lung cancer (Forrest et al, 2003;Kasymjanova et al, 2010;Leung et al, 2012;Trape et al, 2012;Gagnon et al, 2013;Jafri et al, 2013;Ulas et al, 2014). In these studies, prognostic risk models were created using a number of clinical and laboratory variables and low serum albumin level was found to be one of the poor prognostic factors in the majority of the scoring systems.…”
Section: 5971 Serum Albumin As a Prognostic Factor With Stage Iiib Nmentioning
confidence: 99%
“…With the introduction of recent findings, the Glasgow Prognostic Score (GPS) and the Advanced Lung Cancer Inflammation Index (ALI) on the basis of serum albumin and CRP level have been developed. In addition, further scoring systems such as modified-GPS, Prognostic Index (PI), Adverse Prognostic Factors (APF), and the Montreal Prognostic Score (MPS) based on the performance status, CRP, tumor markers such as carbohydrate antigen (CA)-125, and inflammatory markers such as leukocycte and neutrophil/lymphocyte ratio have been developed (Forrest et al, 2003;Kasymjanova et al, 2010;Leung et al, 2012;Trape et al, 2012;Gagnon et al, 2013;Jafri et al, 2013;Ulas et al, 2014). In the majority of these studies, many patients had a metastatic disease (Forrest et al, 2003;Kasymjanova et al, 2010;Leung et al, 2012;Trape et al, 2012;Gagnon et al, 2013;Jafri et al, 2013;Ulas et al, 2014).…”
Section: 5971 Serum Albumin As a Prognostic Factor With Stage Iiib Nmentioning
confidence: 99%
“…Subsequently, many studies investigating the role of serum CYFRA 21-1 with more updated therapeutic strategies for NSCLC and larger numbers of accrued patients have been performed16171819202122232425262728293031323334353637383940414243444546. However, these studies yielded conflicting results.…”
mentioning
confidence: 99%